2016
DOI: 10.1002/app.43700
|View full text |Cite
|
Sign up to set email alerts
|

High‐performance PDMS membranes for pervaporative removal of VOCs from water: The role of alkyl grafting

Abstract: To improve the pervaporation performance of PDMS membrane, alkyl groups with different chain length were grafted into PDMS matrix. The prepared membranes were characterized by ATR-IR, DSC, TGA, PALS, and tensile testing. The effects of alkyl grafting on pervaporation performance of PDMS membrane were investigated in separation of ethyl acetate/water mixture. Experimental results show that the separation factor of PDMS membrane is largely improved by alkyl grafting because of the enhanced preferential sorption … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 54 publications
1
9
0
Order By: Relevance
“…Second, alkyl modified PHMS was cross-linked and grafted homogenously into vinyl terminated polydimethylsiloxane. The results confirmed that alkyl grafted PDMS separation performance depends on both the alkyl grafting ratio and alkyl chain length [20]. Investigations on the effect of alkyl grafting on both separation factor and total flux have been discussed in previous studies.…”
Section: A Pervaporation Membranessupporting
confidence: 78%
See 2 more Smart Citations
“…Second, alkyl modified PHMS was cross-linked and grafted homogenously into vinyl terminated polydimethylsiloxane. The results confirmed that alkyl grafted PDMS separation performance depends on both the alkyl grafting ratio and alkyl chain length [20]. Investigations on the effect of alkyl grafting on both separation factor and total flux have been discussed in previous studies.…”
Section: A Pervaporation Membranessupporting
confidence: 78%
“…Flux rates were associated with the free volume that is explained by the solubility and diffusivity of EA and water in membranes based on the solution-diffusion model. The octyl grafted PDMS membrane (C8-PDMS) showed an improved separation performance in removal of BA, MTBE, and BuOH from water [20]. Fig.…”
Section: A Pervaporation Membranesmentioning
confidence: 99%
See 1 more Smart Citation
“…43 In addition, the decomposition rates of DDHAC from PGD135, 165, and 185 were 9, 16, and 23 wt %, respectively. This was attributed to the better thermal stability in comparison to non-grafted PEAA.…”
Section: Articlementioning
confidence: 95%
“…The first reported use of PV for VOC removal was in 1970 by Cole et al [46], with numerous reports since then showing further developments in the field [45]. A great number of PV membranes investigated for the removal of VOCs have been formed from organophilic materials such as poly[1-(trimethylsilyl)-1-propyne] (PTMSP), polydimethylsiloxane (PDMS), poly (ether-block-amide) (PEBA), and polyvinylidene fluoride (PVDF) [47][48][49][50][51][52][53][54], with many of these polymers and their derivatives being used in industrial settings [55][56][57][58]. The removal of organics from water is also of interest for industrial biotechnology, in particular for the recovery of products such as ethanol, butanol and acetone from fermentation broths, where the concentration of organics is low because of their toxicity towards the microorganisms used for fermentation [59,60].…”
Section: Aqueous-organic Separationsmentioning
confidence: 99%